Quantifying microplastics and their retention in greywater treatment systems of different scales - M. Sami; A. Hedström; H. Österlund; E. Kvarnström; P.D. Jenssen; M. Hartl; I. Herrmann (Journal of Hazardous Materials, 2026)

Pre- and post-harvest spectral estimation of carnosic acid and rosmarinic acid in rosemary - A. Mishra; A. Krief; M.M. Sahoo; A. Schachter; I. Gonda; N. Dudai; T. Trigano; I. Herrmann (Computers and Electronics in Agriculture, 2026)

Aligning Event-Related Potentials with Transcranial Alternating Current Stimulation for Modulation—a Review - Cindy Boetzel; Heiko I. Stecher; Christoph S. Herrmann (Brain Topography, 2024)
This review aims to demonstrate the connections between event-related potentials (ERPs), event-related oscillations (EROs), and non-invasive brain stimulation (NIBS), with a specific focus on transcranial alternating current stimulation (tACS). We begin with a short examination and discussion of the relation between ERPs and EROs. Then, we investigate the diverse fields of NIBS, highlighting tACS as a potent tool for modulating neural oscillations and influencing cognitive performance. Emphasizing the impact of tACS on individual ERP components, this article offers insights into the potential of conventional tACS for targeted stimulation of single ERP components. Furthermore, we review recent articles that explore a novel approach of tACS: ERP-aligned tACS. This innovative technique exploits the temporal precision of ERP components, aligning tACS with specific neural events to optimize stimulation effects and target the desired neural response. In conclusion, this review combines current knowledge to explore how ERPs, EROs, and NIBS interact, particularly highlighting the modulatory possibilities offered by tACS. The incorporation of ERP-aligned tACS introduces new opportunities for future research, advancing our understanding of the complex connection between neural oscillations and cognitive processes.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Integrating animals, pasture, and crops within AusFarm for modelling mixed farming - Neville I. Herrmann; Andrew D. Moore; Eric Zurcher (Environmental Modelling & Software, 2024)

Greywater treatment in a green wall using different filter materials and hydraulic loading rates - M. Sami; A. Hedström; E. Kvarnström; D.T. McCarthy; I. Herrmann (Journal of Environmental Management, 2023)

Evaluation of biotransformation capacity of transplastomic plants and hairy roots of Nicotiana tabacum expressing human cytochrome P450 2D6 - Y. V. Sheludko; I. M. Gerasymenko; F. J. Herrmann; H. Warzecha (Transgenic Research, 2022)
Cytochrome P450 monooxygenases (CYPs) are important tools for regio- and stereoselective oxidation of target molecules or engineering of metabolic pathways. Functional heterologous expression of eukaryotic CYPs is often problematic due to their dependency on the specific redox partner and the necessity of correct association with the membranes for displaying enzymatic activity. Plant hosts offer advantages of accessibility of reducing partners and a choice of membranes to insert heterologous CYPs. For the evaluation of plant systems for efficient CYP expression, we established transplastomic plants and hairy root cultures of Nicotiana tabacum carrying the gene encoding human CYP2D6 with broad substrate specificity. The levels of CYP2D6 transcript accumulation and enzymatic activity were estimated and compared with the data of CYP2D6 transient expression in N. benthamiana . The relative level of CYP2D6 transcripts in transplastomic plants was 2–3 orders of magnitude higher of that observed after constitutive or transient expression from the nucleus. CYP2D6 expressed in chloroplasts converted exogenous synthetic substrate loratadine without the need for co-expression of the cognate CYP reductase. The loratadine conversion rate in transplastomic plants was comparable to that in N. benthamiana plants transiently expressing a chloroplast targeted CYP2D6 from the nucleus, but was lower than the value reported for transiently expressed CYP2D6 with the native endoplasmic reticulum signal-anchor sequence. Hairy roots showed the lowest substrate conversion rate, but demonstrated the ability to release the product into the culture medium. The obtained results illustrate the potential of plant-based expression systems for exploiting the enzymatic activities of eukaryotic CYPs with broad substrate specificities.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Accumulation of Traffic-Related Trace Metals in Urban Winter-Long Roadside Snowbanks - S. Moghadas; K. H. Paus; T. M. Muthanna; I. Herrmann; J. Marsalek; M. Viklander (Water, Air, & Soil Pollution, 2015)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

miR-375 gene dosage in pancreatic β-cells: implications for regulation of β-cell mass and biomarker development - Mathieu Latreille; Karolin Herrmanns; Neil Renwick; Thomas Tuschl; Maciej T. Malecki; Mark I. McCarthy; Katharine R. Owen; Thomas Rülicke; Markus Stoffel (Journal of Molecular Medicine, 2015)

Ground-level hyperspectral imagery for detecting weeds in wheat fields - I. Herrmann; U. Shapira; S. Kinast; A. Karnieli; D. J. Bonfil (Precision Agriculture, 2013)

Longitudinal Dispersion Coefficient: Effects of Particle-Size Distribution - Amir Jourak; Vilnis Frishfelds; J. Gunnar I. Hellström; T. Staffan Lundström; Inga Herrmann; Annelie Hedström (Transport in Porous Media, 2013)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

SWIR-based spectral indices for assessing nitrogen content in potato fields - I. Herrmann; A. Karnieli; D. J. Bonfil; Y. Cohen; V. Alchanatis (International Journal of Remote Sensing, 2010)

Effects of selective inactivation of individual genes for low-molecular-mass subunits on the assembly of photosystem II, as revealed by chloroplast transformation: the psbEFLJ operon in Nicotiana tabacum - M. Swiatek; R. E. Regel; J. Meurer; G. Wanner; H. B. Pakrasi; I. Ohad; R. G. Herrmann (Molecular Genetics and Genomics, 2003)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)